Symposium Proceedings statin therapy- shaping the future ? (AstraZeneca, 2004)
Based on a symposium held during the European Society Cardiology Congress in Vienna, Austria in August 2003, the symposium faculty elaborate on these studies and their clinical implications in a series of presentations